2013
DOI: 10.4103/1658-354x.121048
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-guided end-tidal desflurane concentration during living donor liver transplantation

Abstract: Background:The three phases of living donor liver transplantation (LDLT) represent different liver conditions. The aim is to study the required end-tidal desflurane concentration (ET-Des) guided with entropy monitoring for the depth of anesthesia.Methods:After the Ethics and Research Committee approval, 40 patients were included in this prospective study. Anesthesia was maintained with Desflurane-O2-air. State entropy (SE) and Response entropy (RE) were kept between 40 and 60.Results:Age and Model for End-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
6
4
Order By: Relevance
“…[2127] For this reason, the end-tidal desflurane concentration was fixed at 0.6 age-adjusted MAC, and its corresponding BIS values, which represented anesthetic sensitivity, were obtained in the present study. Unlike the results of the previous studies, which reported the highest anesthetic sensitivity in the anhepatic phase by showing the lowest anesthetic requirements to maintain the desired depth of anesthesia during this phase, [1012] our results demonstrated that there was no significant change in anesthetic sensitivity at a constant anesthetic concentration during the 3 phases in the non-TPCS group (Table 4). Despite prolongation of the anhepatic phase by TPCS, the interval change in anesthetic sensitivity remained insignificant (Table 4).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…[2127] For this reason, the end-tidal desflurane concentration was fixed at 0.6 age-adjusted MAC, and its corresponding BIS values, which represented anesthetic sensitivity, were obtained in the present study. Unlike the results of the previous studies, which reported the highest anesthetic sensitivity in the anhepatic phase by showing the lowest anesthetic requirements to maintain the desired depth of anesthesia during this phase, [1012] our results demonstrated that there was no significant change in anesthetic sensitivity at a constant anesthetic concentration during the 3 phases in the non-TPCS group (Table 4). Despite prolongation of the anhepatic phase by TPCS, the interval change in anesthetic sensitivity remained insignificant (Table 4).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to differences in the methods of anesthetic administration, the insignificant change in anesthetic sensitivity during the 3 phases and its insignificant difference between the 2 groups in the present study might have arisen from the difference in the duration of the anhepatic phase between ours and previous studies [10,11] with data regarding the duration of the anhepatic phase. Interestingly, the average duration of the anhepatic phase extended by TPCS (125.9 minutes) was shorter than the average durations (159 [11] and 195 [10] minutes, respectively) found in previous studies, in which TPCS was not applied.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations